Optimal control of an active filter for the reduction of harmonics in the distribution electrical network, using AKAGI theory (Ciencias de la Ingeniería y Aplicadas, 2021)
The objective of this research is to study the harmonic correction of an electrical distribution system to analyze the implementation of an algorithm based on Nonlinear Optimization and Akagi Theory, which deals with instantaneous active and reactive power where currents and voltages of a three-phase three-wire system were expressed vectorally through the use of the Clarke and Park transform while the other theory is based on obtaining an optimal lambda by formulating the nonlinear optimization model and applying the Lagrange theory, applying the conditions of ( KKT). This study was carried out by designing a base model of a simulated electrical system in the SIMULINK program, implementing an active power filter to the system whose main function is the reduction of harmonics in electrical energy distribution networks. The simulations carried out give optimal results when implementing the active power filter, noticeably correcting the harmonics produced by the different loads that cause disturbances to the electrical network.
Keywords: Harmonics; Electronic Distribution System; Simulink; Active Power; Reactive Power; Active Filter; Disturbances; Loads